2016
DOI: 10.1002/hbm.23201
|View full text |Cite|
|
Sign up to set email alerts
|

Neurofeedback training of EEG alpha rhythm enhances episodic and working memory

Abstract: Neurofeedback training (NFT) of the alpha rhythm has been used for several decades but is still controversial in regards to its trainability and effects on working memory. Alpha rhythm of the frontoparietal region are associated with either the intelligence or memory of healthy subjects and are also related to pathological states. In this study, alpha NFT effects on memory performances were explored. Fifty healthy participants were recruited and randomly assigned into a group receiving a 8-12-Hz amplitude (Alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 53 publications
10
100
0
Order By: Relevance
“…Our findings suggest that EEG‐nf based on modulation of alpha EEG power would naturally complement the rtfMRI‐nf targeting the MD/AN. Studies utilizing EEG‐nf for upregulation of alpha (or upper alpha) EEG power have demonstrated improvements in participants’ cognitive and memory performance, including working memory and short term memory (Escolano et al, ; Hanslmayr, Sauseng, Doppelmayr, Schabus, & Klimesch, ; Hsueh, Chen, Chen, & Shaw, ; Nan et al, ; Zoefel, Huster, & Herrmann, ). Changes in resting fMRI functional connectivity following alpha EEG‐nf training have also been reported (Kluetsch et al, ; Nicholson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that EEG‐nf based on modulation of alpha EEG power would naturally complement the rtfMRI‐nf targeting the MD/AN. Studies utilizing EEG‐nf for upregulation of alpha (or upper alpha) EEG power have demonstrated improvements in participants’ cognitive and memory performance, including working memory and short term memory (Escolano et al, ; Hanslmayr, Sauseng, Doppelmayr, Schabus, & Klimesch, ; Hsueh, Chen, Chen, & Shaw, ; Nan et al, ; Zoefel, Huster, & Herrmann, ). Changes in resting fMRI functional connectivity following alpha EEG‐nf training have also been reported (Kluetsch et al, ; Nicholson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Users were able to terminate the training procedure before the end of the procedure by clicking the Disconnect button. At the end of each session, alpha powers and success number of 300-s training episodes displayed on the smartphone to allow user/researcher to develop or establish their strategy through trial-and-error learning [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…So, future research is warranted to further elaborate in a systematic manner on the potential impact of potential confounding factors (e.g., small sample sizes such as in Rasey et al 1995, see below for more details on confounding factors). Besides that, as suggested earlier by Gruzelier (2014b, c), placebo is still rarely used as we encountered it in only six studies (i.e., Bazanova et al 2013;Escolano et al 2014;Guez et al 2015;Hsueh et al 2016;Kober et al 2015;Wang and Hsieh 2013) to demonstrate the statistical superiority of the effect on the NFB training. However, according to the guidelines for the evaluation of clinical efficacy of psychophysiological interventions, the inclusion of control and placebo or sham feedback groups would enhance the validity within the current research field on NFB training (La Vaque et al 2002).…”
Section: Discussionmentioning
confidence: 79%
“…Thetasuppression NFB training in the left parietal-occipital region has been associated with an increase in attentional performance ) while theta augment NFB training showed a positive impact on the memory consolidation Rozengurt et al 2016) and an improvement of attention and working memory performance for normal aging adults and the executive function for young participants (Wang and Hsieh 2013). Upper alpha augment NFB training showed a positive impact on cognitive performance Bazanova et al 2013), semantic memory ), short-term memory frequency (Hsueh et al 2016;Nan et al 2012), and reduced psychoemotional stress . Beta augment NFB training can be used to enhance attentional processing .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation